ANALYSIS OF THE IMPACT OF CULTURAL DIFFERENCES ON INTERNATIONAL MARKETING NOWADAYS - Ruzimuratov Akmal Bakhodirovich (International Journal of Artificial Intelligence for Digital Marketing, 2024)
This research examines the impact of cultural differences on international marketing and its relevance,based on literary sources and authors own suggestions in this environment for its improvement.